Body weight gain in patients with bilateral deep brain stimulation for dystonia - Wolf, Marc; Ebert, Anne; Hennerici, Michael G.; Blahak, Christian (Journal of neural transmission, 2016)
In patients with Parkinson’s disease, significant weight gain following chronic deep brain stimulation (DBS) has been reported. Recently, relevant weight gain could be demonstrated also following subthalamic nucleus DBS in patients with primary cervical dystonia. Prospective analyses of body weight changes following DBS in patients with dystonia, however, have not been published so far. We aimed to analyse the changes of body weight following DBS in patients with dystonia. The body mass index (BMI) of 17 consecutive patients with segmental or generalised dystonia (mean age 54.6 ± 16.1 years) treated with bilateral DBS of the globus pallidus internus (GPi) (n = 14) or the thalamic ventral intermediate nucleus (n = 3) was measured preoperatively (pre-OP) and at three follow-up (FU) time points post-DBS surgery (FU1 = 7 months, FU2 = 17 months, FU3 = 72 months). All patients benefited from marked improvement in their dystonia. The mean BMI pre-OP (SD) was 22.5 (±3.7) kg/m2 and increased stepwise to 24.0 (±3.3) kg/m2 at FU1, 24.4 (±3.7) kg/m2 at FU2 and 24.9 (±3.7) kg/m2 at FU3 (p < 0.05 at all three FUs compared to pre-OP). Relative BMI increase and improvement of dystonia were correlated (p = 0.025). Chronic bilateral GPi DBS in patients with dystonia is associated with significant body weight gain, in particular during the first 6 months post-OP. This probably is a result of improvement of dystonic motor symptoms and recovery of eating dysfunction rather than a target-specific phenomenon.
Gesehen am 28.03.2019
Published online: 22 August 2015